Time‐lapse systems for embryo incubation and assessment in assisted reproduction - Armstrong, Sarah (Cochrane Database Syst Rev, 2018)
BACKGROUND: Embryo incubation and assessment is a vital step in assisted reproductive technology (ART). Traditionally, embryo assessment has been achieved by removing embryos from a conventional incubator daily for quality assessment by an embryologist, under a light microscope. Over recent years time‐lapse systems have been developed which can take digital images of embryos at frequent time intervals. This allows embryologists, with or without the assistance of embryo selection software, to assess the quality of the embryos without physically removing them from the incubator. The potential advantages of a time‐lapse system (TLS) include the ability to maintain a stable culture environment, therefore limiting the exposure of embryos to changes in gas composition, temperature and movement. A TLS has the potential advantage of improving embryo selection for ART treatment by utilising additional information gained through continuously monitoring embryo development. Use of a TLS often adds significant extra cost onto an in vitro fertilisation (IVF) cycle. OBJECTIVES: To determine the effect of a TLS compared to conventional embryo incubation and assessment on clinical outcomes in couples undergoing ART. SEARCH METHODS: We used standard methodology recommended by Cochrane. We searched the Cochrane Gynaecology and Fertility (CGF) Group trials register, CENTRAL, MEDLINE, Embase, CINAHL and two trials registers on 2 August 2017. SELECTION CRITERIA: We included randomised controlled trials (RCTs) in the following comparisons: comparing a TLS, with or without embryo selection software, versus conventional incubation with morphological assessment; and TLS with embryo selection software versus TLS without embryo selection software among couples undergoing ART. DATA COLLECTION AND ANALYSIS: We used standard methodological procedures recommended by Cochrane. The primary review outcomes were live birth, miscarriage and stillbirth. Secondary outcomes were clinical pregnancy and cumulative clinical pregnancy. We reported quality of the evidence for important outcomes using GRADE methodology. We made the following comparisons. TLS with conventional morphological assessment of still TLS images versus conventional incubation and assessment TLS utilising embryo selection software versus TLS with conventional morphological assessment of still TLS images TLS utilising embryo selection software versus conventional incubation and assessment MAIN RESULTS: We included eight RCTs (N = 2303 women). The quality of the evidence ranged from very low to moderate. The main limitations were imprecision and risk of bias associated with lack of blinding of participants and researchers, and indirectness secondary to significant heterogeneity between interventions in some studies. There were no data on cumulative clinical pregnancy. TLS with conventional morphological assessment of still TLS images versus conventional incubation and assessment There is no evidence of a difference between the interventions in terms of live birth rates (odds ratio (OR) 0.73, 95% CI 0.47 to 1.13, 2 RCTs, N = 440, I(2) = 11% , moderate‐quality evidence) and may also be no evidence of difference in miscarriage rates (OR 2.25, 95% CI 0.84 to 6.02, 2 RCTs, N = 440, I(2) = 44%, low‐quality evidence). The evidence suggests that if the live birth rate associated with conventional incubation and assessment is 33%, the rate with use of TLS with conventional morphological assessment of still TLS images is between 19% and 36%; and that if the miscarriage rate with conventional incubation is 3%, the rate associated with conventional morphological assessment of still TLS images would be between 3% and 18%. There is no evidence of a difference between the interventions in the stillbirth rate (OR 1.00, 95% CI 0.13 to 7.49, 1 RCT, N = 76, low‐quality evidence). There is no evidence of a difference between the interventions in clinical pregnancy rates (OR 0.88, 95% CI 0.58 to 1.33, 3 RCTs, N = 489, I(2) = 0%, moderate‐quality evidence). TLS utilising embryo selection software versus TLS with conventional morphological assessment of still TLS images No data were available on live birth or stillbirth. We are uncertain whether TLS utilising embryo selection software influences miscarriage rates (OR 1.39, 95% CI 0.64 to 3.01, 2 RCTs, N = 463, I(2) = 0%, very low‐quality evidence) and there may be no difference in clinical pregnancy rates (OR 0.97, 95% CI 0.67 to 1.42, 2 RCTs, N = 463, I(2) = 0%, low‐quality evidence). The evidence suggests that if the miscarriage rate associated with assessment of still TLS images is 5%, the rate with embryo selection software would be between 3% and 14%. TLS utilising embryo selection software versus conventional incubation and assessment There is no evidence of a difference between TLS utilising embryo selection software and conventional incubation improving live birth rates (OR 1.21, 95% CI 0.96 to 1.54, 2 RCTs, N = 1017, I(2) = 0%, very low‐quality evidence). We are uncertain whether TLS influences miscarriage rates (OR 0.73, 95% CI 0.49 to 1.08, 3 RCTs, N = 1351, I(2) = 0%, very low‐quality evidence). The evidence suggests that if the live birth rate associated with no TLS is 38%, the rate with use of conventional incubation would be between 36% and 58%, and that if miscarriage rate with conventional incubation is 9%, the rate associated with TLS would be between 4% and 10%. No data on stillbirths were available. It was uncertain whether the intervention influenced clinical pregnancy rates (OR 1.17, 95% CI 0.94 to 1.45, 3 RCTs, N = 1351, I(2) = 42%, very low‐quality evidence). AUTHORS' CONCLUSIONS: There is insufficient evidence of differences in live birth, miscarriage, stillbirth or clinical pregnancy to choose between TLS, with or without embryo selection software, and conventional incubation. The studies were at high risk of bias for randomisation and allocation concealment, the result should be interpreted with extreme caution.